1968
DOI: 10.1017/s0007485300056790
|View full text |Cite
|
Sign up to set email alerts
|

The absorption and storage of insecticide by the in utero larva of the tsetse fly Glossina Pallidipes Aust

Abstract: The present investigation was carried out to determine whether the susceptibility of the pregnant female tsetse fly to DDT and other chlorinated hydrocarbon insecticides could possibly be influenced by the presence in the uterus of the developing larva. Burnett (1962) has shown that pregnant females of Olossina morsitans Westw. exhibit an appreciable increase in tolerance to topically applied DDT compared with males and virgin females, and has suggested the possibility of detoxication of absorbed insecticide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
(7 reference statements)
3
10
0
Order By: Relevance
“…The present evidence that non-viability of the offspring of mothers treated, especially, with organochlorines was due to diversion of insecticide from the maternal haemolymph to the gut of the avidly feeding in utero larva supports the suggestion of Irving [1968] and is consistent with the find-249 ing of Kwan et al [1982] that tolerance of endosulfan was maximal in flies treated on the penultimate day of each pregnancy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present evidence that non-viability of the offspring of mothers treated, especially, with organochlorines was due to diversion of insecticide from the maternal haemolymph to the gut of the avidly feeding in utero larva supports the suggestion of Irving [1968] and is consistent with the find-249 ing of Kwan et al [1982] that tolerance of endosulfan was maximal in flies treated on the penultimate day of each pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…Increased insecticide-tolerance by pregnant tsetse, compared with non-pregnant specimens, was shown for several species and insecticides [Burnett, 1962;Hadaway, 1972;Irving, 1968;Kwan et al, 1982] and Irving [1968] suggested that diversion of absorbed insecticide into in utero larvae protected pregnant flies from lethal action. Davies [1978] showed that all flies (Glossina morsitans centralis Machado) surviving endosulfan-spraying in Botswana were pregnant and mentioned the usefulness of knowing the fate of the progeny of these flies.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant tsetse have greatly raised tolerance t o topical applications of insecticide, because a large part of the dose is diverted t o the larva in utero (Irving, 1968). This is assumed to be the reason that the only tsetse flies that consistently survive non-residual, aerosol insecticide sprays in the field are pregnant females (Davies, 1978).…”
Section: Potential Insecticide Avoidancementioning
confidence: 99%
“…This gives rise to a further problem: the fate of the larvae that they are carrying. It appears that at least part of a pregnant female's increased resistance is due to the ability to excrete insecticide into the 'milk' supplied to the larva (Irving, 1968). It would be useful to know whether larvae can survive this since, if they can, an aerial spraying programme would have to be adapted not only to eliminate survivors but also the offspring of survivors.…”
Section: Modification To Improve the Aerial Spraying Techniquementioning
confidence: 99%